2022
DOI: 10.3390/chemosensors10060211
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Au@ZnO Nanofilms by Combining Magnetron Sputtering and Post-Annealing for Selective Detection of Isopropanol

Abstract: We demonstrate the highly sensitive and fast response/recovery gas sensors for detecting isopropanol (IPA), in which the Au-nanoparticles-modified ZnO (Au@ZnO) nanofilms act as the active layers. The data confirm that both the response and the response/recovery speed for the detection of IPA are significantly improved by adding Au nanoparticles on the surface of ZnO nanofilms. The gas sensor with an Optimum Au@ZnO nanofilm exhibits the highest responses of 160 and 7 to the 100 and 1 ppm IPA at 300 °C, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Wang et al demonstrated the sensor based on p-NiO/n-ZnO also showed good selectivity, high response (R a /R g = 221.3 to 400 ppm IPA) and fast response rate (less than 10 s) [9]. In our previous work, IPA sensors based on Au functionalized ZnO nanofilms were also obtained, which showed a low detection limit of 1 ppm at 300 °C, needing further to be improved [10]. As mentioned above, ZnO based sensitive materials prepared by chemical synthesis methods exhibit good sensing properties for IPA, but there are still some urgent issues that need to be addressed, such as poor repeatability, complex preparation process, and susceptibility of the sensing layer to detachment from the electrodes.…”
Section: Introductionmentioning
confidence: 89%
“…Wang et al demonstrated the sensor based on p-NiO/n-ZnO also showed good selectivity, high response (R a /R g = 221.3 to 400 ppm IPA) and fast response rate (less than 10 s) [9]. In our previous work, IPA sensors based on Au functionalized ZnO nanofilms were also obtained, which showed a low detection limit of 1 ppm at 300 °C, needing further to be improved [10]. As mentioned above, ZnO based sensitive materials prepared by chemical synthesis methods exhibit good sensing properties for IPA, but there are still some urgent issues that need to be addressed, such as poor repeatability, complex preparation process, and susceptibility of the sensing layer to detachment from the electrodes.…”
Section: Introductionmentioning
confidence: 89%
“…Functionalizing ZnO with Au can also profoundly influence the detection limit of the ZnO sensor for target gases, with some samples demonstrating detection capabilities in the ppb range. Wang et al 87 reported the use of Au/ZnO nanofilm for isopropanol sensing, with the sensor exhibiting a high response of 160 to 100 ppm isopropanol and 7 to 1 ppm isopropanol at 300 °C, displaying surprising response and lower detection limits. Saito et al 88 reported a pyramid-shaped ZnO particle loaded with Au NPs for detecting isoprene.…”
Section: Mos Functionalized With Au Npsmentioning
confidence: 99%
“…The optimum working temperature was reduced with the increasing concentration of Au modification, and the response/recovery times were also shortened. 30 The advancement of the gas-sensing performances could be ascribed to the sensitization of Au, whereby Au NPs promote the conversion of oxygen molecules, leading to more oxygen ions reacting with the target gas and achieving an enhancement in the gas-sensitive response. Besides, the synergistic electronic interactions between Au ( φ = 5.1 eV) and α-Fe 2 O 3 ( φ = 5.88 eV) can also thicken the electron-depletion layer on the surface, 31 thus improving the sensing performance.…”
Section: Introductionmentioning
confidence: 99%